A review of the Grapsid crab genus Sesarma (Crustacea: Decapoda Grapsidae) in America, with the description of a new genus - Abele, Lawrence G. (Washington, D.C. Smithsonian Institution, 1984)
Smithsonian contributions to zoology; no. 527
Keywords: Armases--America--Classification.; Sesarma--America--Classification.